Kajian Deskriptif Penyelenggaraan Kurikulum Muatan Lokal Bahasa Using Di SDN 1 Kertosari Banyuwangi - Andrea Yurista Tyasari; Anselmus JE Toenlioe; Yerry Soepriyanto (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2017)
The research objective is to describe the planning of the local content curriculum components as well as to describe the implementation of the local content curriculum in schools. This research use desciptive qualitative approach. The results showed that the implementation of local content in primary schools has many obstacles. The problems in implementing the local content curriculum to date relate to all aspects of planning, implementation and evaluation. Currently, it is very necessary to conduct a review of the implementation of the local content curriculum in Using Language and it requires evaluation as well as a comprehensive renewal. Research will provide input on existing programs.